REKAYASA SISTEM INFORMASI FASILITAS PARKIR BERLANGGANAN DI KAMPUS SUDIRMAN UNIVERSITAS UDAYANA BERBASIS ANDROID - Febrianto Dhembi, Ricardus; Rian Pranajaya, I Putu; Matheus Arjuna, Yafier; Sudarma, Made; Care Khrisne, Duman; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 11 No 3 (2024): Jurnal SPEKTRUM, 2024)
Parking facilities have become a crucial component in this era of mobility. The increasing number of vehicles each year has led to a growing demand for parking spaces. Parking facilities must meet several criteria, such as guaranteed security, adequate land, and good management to ensure drivers feel comfortable leaving their vehicles. The Sudirman Campus of Udayana University has adequate parking space at various corners of the campus for both two-wheeled and four-wheeled vehicles. However, the availability of adequate parking facilities is not proportional to good management and security supervision. This often leads to various problems, ranging from overload to security issues. Therefore, an integrated parking management system is needed to ensure that the use of parking spaces at the Sudirman Campus is more orderly, targeted, and secure. In this study, the author designs an integrated parking management system for the Sudirman Campus that utilizes technology. This system has two main components: an Android-based parking facility information system and a prototype automatic gate. The Android application is built using the Flutter framework and utilizes QR Code technology, which is a development of Barcode. Meanwhile, the automatic gate prototype is built based on the Internet of Things and serves as a trial before the actual design of the automatic gate.